GAMBARAN PENGETAHUAN REMAJA TENTANG DAMPAK PERNIKAHAN DINI PADA KESEHATAN REPRODUKSI DI SMAS AL AZHAR PRIGEN KABUPATEN PASURUAN - Adyani, Asta (Sinar : Jurnal Kebidanan, 2024)
Background: Early marriage has an impact on sexual relations at an early age, complications of pregnancy and childbirth. Efforts to increase knowledge about the impact of early marriage on reproductive health are urgently needed, one of which is to avoid the high prevalence of early marriage. Objective: The purpose of this study was to describe the level of knowledge of adolescents about the impact of early marriage on reproductive health. Methods: The type of research used is descriptive using a quantitative approach. This research was conducted in June 2023 at SMAS Al-Azhar Prigen, Pasuruan Regency. The sampling technique uses a sampling quota with a total of 57 youth. Results: The results showed that the majority of adolescents had a good level of knowledge of 40 people (70.2%), the sufficient category was 11 people (19.3%), and the poor category was 6 people (10.5%). Conclusion: The conclusion of this study is that most adolescents have good knowledge about the impact of early marriage on reproductive health. Good knowledge can influence the attitude of adolescents in making decisions to prevent early marriage, so that it can contribute to reducing the high prevalence of early marriage which has a negative impact on reproductive health.